Les pilotes à l'épreuve du confinement : activités, expériences et pratiques professionnelles des personnels d'encadrement et des directeurs et directrices d'école - Diane Béduchaud (Nantes Université, 2022)
The lockdown has drastically changed the work conditions of all those involved in education, and in particular those of the managers (school principals, directors and principals) in charge of implementing national regulations on the ground and ensuring the governance of schools during this period of unprecedented change. The closure of schools and the introduction of the "pedagogical continuity" have joined the tendencies that already affect the management professions and their activities in their ordinary working life, in particular the difficulty of managing a heavy workload and the gap between the prescriptions and the reality. This period helped to redefine their relations within the teaching community, revealing a deterioration in relations with a "hierarchy" deemed too "top-down". This period was also a source of satisfying professional transformation, with a perceived improvement in "horizontal" relations (peers, families), and an organisational shift marked by greater control over working time.